2016
DOI: 10.1093/pcp/pcw159
|View full text |Cite
|
Sign up to set email alerts
|

Sulfoquinovosyldiacylglycerol has an Essential Role inThermosynechococcus elongatusBP-1 Under Phosphate-Deficient Conditions

Abstract: Anionic lipids, sulfoquinovosyldiacylglycerol (SQDG) and phosphatidylglycerol (PG), are major classes of the thylakoid membrane lipids in cyanobacteria and plant chloroplasts. PG is essential for growth and photosynthesis of cyanobacteria, algae and plants, but the requirement for SQDG differs even among cyanobacterial species. Although SQDG and PG can compensate each other in part presumably to maintain proper balance of anionic charge in lipid bilayers, the functional relationship of these lipids is largely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 54 publications
2
27
0
Order By: Relevance
“…The results showed that the oxygen-evolving activity of the mutant samples decreased by about 19 -32% in the thylakoid membranes and purified PSII dimers. This decrease is comparable with those observed with the mutant cells of T. elongatus reported previously (3) and also with the previous report in the C. reinhardtii mutant with the SQDG synthesis gene inactivated (15)(16)(17). To examine the causes for the decrease of PSII activity in detail, we performed spectroscopic analyses with the WT and ⌬sqdB samples.…”
Section: Analyses On the Content Of Psii Dimer And Oxygen Evolutionsupporting
confidence: 89%
See 4 more Smart Citations
“…The results showed that the oxygen-evolving activity of the mutant samples decreased by about 19 -32% in the thylakoid membranes and purified PSII dimers. This decrease is comparable with those observed with the mutant cells of T. elongatus reported previously (3) and also with the previous report in the C. reinhardtii mutant with the SQDG synthesis gene inactivated (15)(16)(17). To examine the causes for the decrease of PSII activity in detail, we performed spectroscopic analyses with the WT and ⌬sqdB samples.…”
Section: Analyses On the Content Of Psii Dimer And Oxygen Evolutionsupporting
confidence: 89%
“…The roles of lipids can be classified in two ways: one is to form the lipid bilayer, and the other one is to associate with some specific sites of membrane protein(s) to function as an essential part of that protein(s). MGDG and DGDG are nonionic lipids and are considered to function mainly as structural lipids for the formation of the lipid bilayer, whereas SQDG and PG are acidic lipids and are probably required to maintain the balance of negative charges in the thylakoid membranes (3,4). In addition, all of these lipids are found to bind directly to photosynthetic membrane-protein complexes, such as photosystem II (PSII), photosystem I (PSI), and cytochrome b 6 f (5)(6)(7)(8), and therefore may be required to maintain the integral functions of these protein complexes.…”
Section: Sulfoquinovosyl-diacylglycerol (Sqdg) Is One Of the Four Lipmentioning
confidence: 99%
See 3 more Smart Citations